2007
DOI: 10.1348/026151006x171343
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic aspects of communication and language comprehension in groups of children differentiated by teacher ratings of inattention and hyperactivity

Abstract: Please contact Kate Cain for a copy of this paper.Inattention, hyperactivity and pragmatic language skills page 2 AbstractChildren with attention deficit hyperactivity disorder (ADHD) experience pragmatic language deficits, but it is not known whether these difficulties are primarily associated with high levels of inattention, hyperactivity, or both. We investigated pragmatic aspects of communication and language comprehension in relation to poor attention and/or high hyperactivity in a nondiagnosed population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 33 publications
(48 reference statements)
6
81
0
3
Order By: Relevance
“…The extent of pragmatic language difficulties was related to the hyperactivity characteristics, but not to the attention difficulties the parents reported. These findings were in line with the findings of Bignell and Cain (2007). These authors reported pragmatic language deficits in each of the three AD/ HD subtypes, but the deficits were more profound in those children that were hyperactive and impulsive (irrespective of whether they also had attention deficits as for both groups large effect sizes were obtained) than in the children that had attention deficits only (as only small effect sizes were obtained).…”
Section: Pragmatic Abilities In Ad/hdsupporting
confidence: 88%
See 3 more Smart Citations
“…The extent of pragmatic language difficulties was related to the hyperactivity characteristics, but not to the attention difficulties the parents reported. These findings were in line with the findings of Bignell and Cain (2007). These authors reported pragmatic language deficits in each of the three AD/ HD subtypes, but the deficits were more profound in those children that were hyperactive and impulsive (irrespective of whether they also had attention deficits as for both groups large effect sizes were obtained) than in the children that had attention deficits only (as only small effect sizes were obtained).…”
Section: Pragmatic Abilities In Ad/hdsupporting
confidence: 88%
“…A striking finding was that children with AD/HD hardly differed from children with autism. These observed pragmatic difficulties in AD/HD children have been replicated in various other studies (Bignell & Cain, 2007;Bruce, Thernlund, & Nettelbladt, 2006;Geurts & Embrechts, 2008;Geurts et al, 2004b;Norbury, Nash, Baird, & Bishop, 2004). The pragmatic difficulties in children with ADHD were, in general, less profound compared to those observed in children with autism for whom pragmatic language deficits are a key characteristic (American Psychiatric Association, 2000).…”
Section: Executive Functions Theory Of Mind and Pragmatic Abilitiessupporting
confidence: 52%
See 2 more Smart Citations
“…For example, teachers and parents of children with ADHD sometimes report that these children incorrectly interpret figurative language, such as expressions, in a literal manner. However, children with ADHD do not differ from controls on formal tests of semantic knowledge, such as those that require defining words in various context (Bignell & Cain, 2007;Bishop, 1998;Purvis & Tannock, 1997).…”
Section: Adhd and Languagementioning
confidence: 99%